Carbon-coated iron-cobalt nano-particles with high saturation magnetization and low coercive force as well as preparation method and application of carbon-coated iron-cobalt nano-particles

By preparing carbon-coated iron-cobalt nanoparticles, the problem of unstable magnetic properties of iron-cobalt nanoalloys was solved, achieving high saturation magnetization and low coercivity, making it suitable for high-frequency and complex devices.

CN120854154APending Publication Date: 2025-10-28HEFEI UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511146893.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-15
Publication Date
2025-10-28

AI Technical Summary

Technical Problem

Existing iron-cobalt nanoalloys have poor magnetic property repeatability, and the nanoparticles are easily oxidized and accumulate under magnetic fields, making it difficult to meet the low-loss requirements in high-frequency scenarios.

Method used

Using ferric nitrate, cobalt salt, and 2-methylimidazole as raw materials, carbon-coated iron-cobalt nanoparticles were prepared by rotary evaporation followed by pyrolysis under inert gas protection. This process controlled the distribution of iron and cobalt elements and formed a carbon shell for protection, thus inhibiting oxidation and accumulation.

Benefits of technology

Carbon-coated iron-cobalt nanoparticles with high saturation magnetization and low coercivity were prepared, which are suitable for high-frequency devices and complex devices, and have good repeatability and stability, making them suitable for industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120854154A_ABST
    Figure CN120854154A_ABST
Patent Text Reader

Abstract

The invention discloses carbon-coated iron-cobalt nanoparticles with high saturation magnetization and low coercive force as well as a preparation method and application of the carbon-coated iron-cobalt nanoparticles. The preparation method comprises the following steps: mixing ferric nitrate and / or ferrous nitrate, cobalt salt, 2-methylimidazole and a solvent, stirring, and spin-drying to obtain an iron-cobalt bimetallic complex precursor; the molar ratio of ferric nitrate and / or ferrous nitrate to cobalt salt is (1-3): (1-2); the molar ratio of ferric nitrate and / or ferrous nitrate to 2-methylimidazole is 1: (1-25); and pyrolyzing the iron-cobalt bimetallic complex precursor in inert gas at 850-950 DEG C to obtain the carbon-coated iron-cobalt nanoparticles with high saturation magnetization and low coercive force. The method is mild in condition, simple in process and easy for large-scale production, and the graphitized carbon layer of the material can isolate oxygen and a corrosive medium and maintain high Ms of the iron-cobalt core; the electron coupling effect of the carbon shell and the iron-cobalt interface can reduce lattice distortion, inhibit magnetic domain wall pinning and reduce coercive force.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of magnetic nanomaterial preparation technology, specifically to a carbon-coated iron-cobalt nanoparticle with high saturation magnetization and low coercivity, its preparation method, and its application. Background Technology

[0002] Traditional soft magnetic materials (such as silicon steel) suffer from high coercivity, making it difficult to meet the low-loss requirements of high-frequency applications. Metal oxide magnetic materials, limited by their theoretical magnetic properties, exhibit only low saturation magnetization, also insufficient for current applications. Iron-cobalt alloys (FeCo) theoretically possess superior magnetic properties, such as high saturation magnetization (theoretical value > 2.4T), high permeability, high Curie temperature, low magnetostriction coefficient, and low coercivity, making them highly promising for magnetic storage devices and sensors. Nanostructuring FeCo alloys not only maintains or even enhances their original magnetic properties but also endows them with new characteristics, such as enhanced surface effects and quantum size effects. These properties make FeCo nanoalloys promising for applications in electromagnetic shielding, flexible sensors, and other fields. Currently, FeCo nanoalloys are synthesized using methods such as chemical co-reduction, vapor deposition, and mechanical ball milling. However, these methods produce FeCo nanoalloys with poor magnetic repeatability, and the magnetic properties of nanoscale FeCo particles are prone to decay due to surface oxidation and magnetic moment disorder. Furthermore, nanoparticles tend to accumulate under long-term use in magnetic fields. Summary of the Invention

[0003] The technical problem to be solved by this invention is how to improve the magnetic properties of iron-cobalt nanoparticle soft magnetic materials.

[0004] The present invention solves the above-mentioned technical problems through the following technical means:

[0005] A method for preparing carbon-coated iron-cobalt nanoparticles with high saturation magnetization and low coercivity includes the following steps:

[0006] S1. Ferric nitrate and / or ferrous nitrate, cobalt salt, 2-methylimidazole are mixed with a solvent, stirred and reacted, and then evaporated to dryness using a rotary evaporator to obtain an iron-cobalt bimetallic complex precursor; wherein, the molar ratio of ferric nitrate and / or ferrous nitrate to cobalt salt is 1-3:1-2; and the molar ratio of ferric nitrate and / or ferrous nitrate to 2-methylimidazole is 1:1-25;

[0007] S2. The iron-cobalt bimetallic complex precursor is pyrolyzed under inert gas protection to obtain the carbon-coated iron-cobalt nanoparticles with high saturation magnetization and low coercivity; wherein the pyrolysis temperature is 850-950℃.

[0008] Preferably, the molar ratio of ferric nitrate and / or ferrous nitrate and cobalt salt is 1-2:1-2.

[0009] Preferably, the molar ratio of ferric nitrate and / or ferrous nitrate to 2-methylimidazole is 1:1.22-24.4, and can be 1:1.22, 1:6, 1:12.2, or 1:24.4.

[0010] Preferably, the ratio of 2-methylimidazole to solvent is 1-20g:200ml.

[0011] Preferably, in S1, the cobalt salt is cobalt nitrate.

[0012] Preferably, in S1, the solvent is methanol.

[0013] Preferably, in S1, the stirring reaction is carried out at room temperature for 10-30 hours.

[0014] Preferably, in S2, the inert gas is one or a mixture of two of nitrogen and argon.

[0015] Preferably, in step S2, the inert gas is argon, and the flow rate is 30-60 mL / min.

[0016] Preferably, in S2, the pyrolysis temperature is 850°C.

[0017] Preferably, in S2, the heating rate during the pyrolysis process is 5°C / min.

[0018] Preferably, in S2, the pyrolysis time is 1-3 hours.

[0019] Preferably, in S1, ferric nitrate, cobalt salt, 2-methylimidazole are mixed with a solvent, stirred and reacted, and then evaporated using a rotary evaporator to obtain the iron-cobalt bimetallic complex precursor.

[0020] This invention uses ferric nitrate and / or ferrous nitrate, cobalt salt, and the organic ligand 2-methylimidazole as raw materials at room temperature. These are mixed uniformly in a solvent in a specific ratio and stirred to ensure a complete reaction. The solution is then rotary evaporated to obtain a blue-purple gel-like product, yielding an iron-cobalt bimetallic complex precursor. This precursor ensures a uniform and stable distribution of iron and cobalt metal elements in a predetermined ratio. The precursor is then pyrolyzed under an inert gas atmosphere. During pyrolysis, the ligand releases a reducing atmosphere, causing iron and cobalt ions to be reduced in situ and locally condensed into iron-cobalt alloy nanoparticles in a specific ratio. The resulting organic carbon framework anchors the nanoparticles, preventing them from growing too large, and carbon-coats the alloy particles to prevent oxidation by gases such as oxygen, thus obtaining the desired carbon-coated iron-cobalt nanoalloy particles.

[0021] The present invention also proposes a carbon-coated iron-cobalt nanoparticle with high saturation magnetization and low coercivity, which is prepared by the aforementioned method for preparing carbon-coated iron-cobalt nanoparticles with high saturation magnetization and low coercivity.

[0022] Preferably, carbon-coated iron-cobalt nanoparticles with high saturation magnetization and low coercivity have a saturation magnetization of 105–180 emu / g and a coercivity of 60–140 Oe, and can be used as high-efficiency soft magnetic materials in various fields.

[0023] Preferably, the molar content of iron-cobalt alloy in carbon-coated iron-cobalt nanoparticles with high saturation magnetization and low coercivity is 10% to 40%.

[0024] The nanoparticles of this invention can be used to prepare high-performance iron-cobalt-based composite soft magnetic materials, suitable for various complex, miniaturized, and multifunctional high-power soft magnetic devices, and have broad application prospects. This invention features abundant raw material sources, a simple process, reliable repeatability, low reaction temperature, low energy consumption, and environmental friendliness, making it easy for industrial production.

[0025] The present invention also proposes the application of the carbon-coated iron-cobalt nanoparticles with high saturation magnetization and low coercivity in soft magnetic devices.

[0026] Compared with the prior art, the beneficial effects of the present invention are reflected in:

[0027] 1. This invention utilizes iron and cobalt salts with suitable organic ligands to synthesize iron-cobalt complex precursors, which are iron-cobalt bimetallic imidazole complexes. These precursors are then pyrolyzed under an inert atmosphere to prepare carbon-coated iron-cobalt nanoparticles (FeCo@C). High-performance FeCo@C soft magnetic materials were prepared by adjusting the raw material ratio and pyrolysis temperature. The reaction conditions are mild, energy consumption is low, the synthesis process is simple, and it is easy to mass-produce. The graphitized carbon layer of the material can isolate oxygen and corrosive media, maintaining the high molecular weight of the iron-cobalt core. s (≥105 emu / g); The electronic coupling between the carbon shell and the iron-cobalt interface can reduce lattice distortion and suppress magnetic domain wall pinning, thereby reducing coercivity (≤140 Oe);

[0028] 2. The carbon-coated iron-cobalt nanoalloy particles with high saturation magnetization and low coercivity prepared by this invention utilize a graphite coating layer to regulate the composite structure of the iron-cobalt nanoalloy. The carbon layer inhibits particle agglomeration through van der Waals forces and reduces interfacial stress through matching thermal expansion coefficients, ensuring the long-term stability of the material. Exhibiting high saturation magnetization and low coercivity in soft magnetic devices, these particles have significant application value in power electronics, high-frequency devices, magnetic storage, magnetorheological fluids, and electromagnetic shielding. Attached Figure Description

[0029] Figure 1 This is a scanning electron microscope (SEM) image of the product obtained in Example 1 of the present invention;

[0030] Figure 2 This is a high-resolution transmission electron microscope (HRTEM) image of the product obtained in Example 1 of the present invention;

[0031] Figure 3 The image shows the X-ray photoelectron spectrum (XPS) of the product obtained in Example 1 of this invention.

[0032] Figure 4 The image shows the X-ray diffraction (XRD) pattern of the product obtained in Example 1 of this invention; where black represents the curve of the product in the example.

[0033] Figure 5 The mass spectrum (ESI-MS) of the coordination precursor used in Example 1 of this invention;

[0034] Figure 6 The image shows the hysteresis loop (VSM) of the product obtained in Example 1 of this invention.

[0035] Figure 7 The image shows the hysteresis loop (VSM) of the product obtained in Example 2 of this invention.

[0036] Figure 8 The image shows the hysteresis loop (VSM) of the product obtained in Example 3 of this invention.

[0037] Figure 9 The image shows the hysteresis loop (VSM) of the product obtained in Example 4 of this invention.

[0038] Figure 10 The image shows the hysteresis loop (VSM) of the product obtained in Example 5 of this invention.

[0039] Figure 11 The image shows the hysteresis loop (VSM) of the product obtained in Comparative Example 1 of this invention.

[0040] Figure 12 The image shows the hysteresis loop (VSM) of the product obtained in Comparative Example 2 of this invention. Detailed Implementation

[0041] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions of the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0042] Unless otherwise specified, all test materials and reagents used in the following examples are commercially available.

[0043] Unless otherwise specified in the embodiments, the techniques or conditions described in the literature in this field or in accordance with the product manual may be followed.

[0044] All chemical reagents used in the following examples are chemically pure and readily available on the market.

[0045] The ferric nitrate mentioned is ferric nitrate nonahydrate (Fe(NO3)3·9H2O), and the cobalt nitrate mentioned is cobalt nitrate hexahydrate (Co(NO3)2·6H2O).

[0046] Example 1

[0047] A method for preparing carbon-coated iron-cobalt nanoparticles with high saturation magnetization and low coercivity includes the following steps:

[0048] (1) Add 4g (10mmol) of ferric nitrate, 1.45g (5mmol) of cobalt nitrate and 1g (12.2mmol) of 2-methylimidazole to 200mL of methanol and dissolve by sonication at room temperature.

[0049] (2) Stir the solution obtained in step (1) at room temperature for 24 hours.

[0050] (3) The solution in step (2) was dried by rotary evaporation and vacuum dried to collect the iron-cobalt bimetallic complex precursor.

[0051] (4) The iron-cobalt bimetallic complex precursor obtained in step (3) is heated to 850°C for 2 hours in a tube furnace under argon protection at a flow rate of 30 mL / min to obtain the carbon-coated iron-cobalt nanoparticles with high saturation magnetization and low coercivity.

[0052] The SEM image of the carbon-coated iron-cobalt nanoparticles obtained in this embodiment is shown below. Figure 1 As shown, the product is a layered graphite-coated iron-cobalt nanoalloy structure.

[0053] The high-resolution transmission electron microscope image of the carbon-coated iron-cobalt nanoparticles obtained in this embodiment is shown below. Figure 2 As shown, the lattice spacing of the graphite-coated iron-cobalt nanoalloy is 0.2022 nm, which corresponds to its XRD pattern.

[0054] The XPS image of the carbon-coated iron-cobalt nanoparticles obtained in this embodiment is as follows: Figure 3 As shown, the product contains iron, cobalt, and carbon elements.

[0055] The XRD pattern of the carbon-coated iron-cobalt nanoparticles obtained in this embodiment is as follows: Figure 4 As shown in the figure, it can be seen that the peaks at 2θ of 44.7 and 65.1 are the 110 and 200 crystal planes of the iron-cobalt nano-alloy, respectively.

[0056] The electrospray ionization mass spectrometry (ESI / MS) spectrum of the complex precursor obtained in this embodiment is shown below. Figure 5 As shown, the complex is a complex of cobalt and iron each coordinated with a 2-methylimidazole.

[0057] through Figure 3 and Figure 5 It can be seen that the molar content of iron-cobalt alloy in carbon-coated iron-cobalt nanoparticles is 36%.

[0058] Hysteresis loop tests were performed on the carbon-coated iron-cobalt nanoparticles with high saturation magnetization and low coercivity obtained in this embodiment. The equipment used for this test was a LakeShore 8604 vibrating sample magnetometer (VSM) from the United States. The specific steps were as follows: After the instrument was powered on and warmed up for half an hour, the VSM was calibrated using a Ni standard sample. Then, the sample tube containing the sample was fixed to the sample rod, the sample rod was installed on the VSM vibrating head, and the saddle point was aligned. A suitable test program was selected to start the test. The hysteresis loop diagram of the carbon-coated iron-cobalt nanoparticles with high saturation magnetization and low coercivity obtained in this embodiment is shown below. Figure 6 As shown, the carbon-coated iron-cobalt nanoparticles exhibit a saturation magnetization of 180 emu / g and a coercivity of only 71 Oe. This demonstrates that the carbon-coated iron-cobalt nanoparticles obtained in this embodiment possess both high saturation magnetization and low coercivity.

[0059] Example 2

[0060] In this embodiment, carbon-coated iron-cobalt nanoparticles with high saturation magnetization and low coercivity were prepared using the same method as in Example 1. The difference was that in step (1), the amount of 2-methylimidazole was changed to 2.5 g (30 mmol), iron nitrate was changed to 2 g (5 mmol), and cobalt nitrate was changed to 2.9 g (10 mmol).

[0061] The carbon-coated iron-cobalt nanoparticles with high saturation magnetization and low coercivity obtained in this example were subjected to hysteresis loop testing using the same method as in Example 1. Figure 7 As shown, at room temperature, the saturation magnetization of the carbon-coated iron-cobalt nanoparticles in this embodiment is 171 emu / g, and its coercivity is 127 Oe.

[0062] Example 3

[0063] In this embodiment, carbon-coated iron-cobalt nanoparticles with high saturation magnetization and low coercivity were prepared using the same method as in Example 1, except that the amount of 2-methylimidazole in step (1) was changed to 10g (122mmol).

[0064] The carbon-coated iron-cobalt nanoparticles with high saturation magnetization and low coercivity obtained in this example were subjected to hysteresis loop testing using the same method as in Example 1. Figure 8 As shown, at room temperature, the saturation magnetization of the carbon-coated iron-cobalt nanoparticles in this embodiment is 142 emu / g, and its coercivity is 132 Oe.

[0065] Example 4

[0066] In this embodiment, carbon-coated iron-cobalt nanoparticles with high saturation magnetization and low coercivity were prepared using the same method as in Example 1, except that the amount of 2-methylimidazole in step (1) was changed to 20g (244mmol).

[0067] The carbon-coated iron-cobalt nanoparticles with high saturation magnetization and low coercivity obtained in this example were subjected to hysteresis loop testing using the same method as in Example 1. Figure 9 As shown, at room temperature, the saturation magnetization of the carbon-coated iron-cobalt nanoparticles in this embodiment is 105 emu / g, and its coercivity is 63 Oe.

[0068] Example 5

[0069] In this embodiment, carbon-coated iron-cobalt nanoparticles with high saturation magnetization and low coercivity are prepared using the same method as in Example 1, except that the pyrolysis temperature in step (4) is changed to 950℃.

[0070] The carbon-coated iron-cobalt nanoparticles with high saturation magnetization and low coercivity obtained in this example were subjected to hysteresis loop testing using the same method as in Example 1. Figure 10 As shown, at room temperature, the saturation magnetization of the carbon-coated iron-cobalt nanoparticles in this embodiment is 144 emu / g, and its coercivity is 63 Oe.

[0071] Comparative Example 1

[0072] This comparative example prepared carbon-coated iron-cobalt nanoparticles with high saturation magnetization and low coercivity using the same method as in Example 1, except that in step (3), the rotary evaporator was changed from rotary drying to centrifugal separation.

[0073] The carbon-coated iron-cobalt nanoparticles obtained in this comparative example were subjected to hysteresis loop testing using the same method as in Example 1. Figure 11 As shown, at room temperature, the saturation magnetization of the carbon-coated iron-cobalt nanoparticles in this comparative example is 91 emu / g, and its coercivity is 253 Oe.

[0074] Comparative Example 2

[0075] This comparative example prepared carbon-coated iron-cobalt nanoparticles using the same method as in Example 1, except that the pyrolysis temperature in step (4) was changed to 650°C.

[0076] The carbon-coated iron-cobalt nanoparticles obtained in this comparative example were subjected to hysteresis loop testing using the same method as in Example 1. Figure 12 As shown, at room temperature, the saturation magnetization of the carbon-coated iron-cobalt nanoparticles in this comparative example is 77 emu / g, while its coercivity is 244 Oe.

[0077] The above embodiments are only used to illustrate the technical solutions of the present invention, and are not intended to limit it. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing carbon-coated iron-cobalt nanoparticles with high saturation magnetization and low coercivity, characterized in that: Includes the following steps: S1. Ferric nitrate and / or ferrous nitrate, cobalt salt, 2-methylimidazole are mixed with a solvent, stirred and reacted, and then evaporated to dryness using a rotary evaporator to obtain an iron-cobalt bimetallic complex precursor; wherein, the molar ratio of ferric nitrate and / or ferrous nitrate to cobalt salt is 1-3:1-2; and the molar ratio of ferric nitrate and / or ferrous nitrate to 2-methylimidazole is 1:1-25; S2. The iron-cobalt bimetallic complex precursor is pyrolyzed under inert gas protection to obtain the carbon-coated iron-cobalt nanoparticles with high saturation magnetization and low coercivity; wherein the pyrolysis temperature is 850-950℃.

2. The method for preparing carbon-coated iron-cobalt nanoparticles with high saturation magnetization and low coercivity according to claim 1, characterized in that: In S1, the cobalt salt is cobalt nitrate.

3. The method for preparing carbon-coated iron-cobalt nanoparticles with high saturation magnetization and low coercivity according to claim 1, characterized in that: In S1, the solvent is methanol.

4. The method for preparing carbon-coated iron-cobalt nanoparticles with high saturation magnetization and low coercivity according to claim 1, characterized in that: In S1, the stirring reaction is carried out at room temperature for 10-30 hours.

5. The method for preparing carbon-coated iron-cobalt nanoparticles with high saturation magnetization and low coercivity according to claim 1, characterized in that: In S2, the inert gas is one or a mixture of two of nitrogen and argon.

6. The method for preparing carbon-coated iron-cobalt nanoparticles with high saturation magnetization and low coercivity according to claim 1, characterized in that: In S2, the pyrolysis time is 1-3 hours.

7. A carbon-coated iron-cobalt nanoparticle with high saturation magnetization and low coercivity, characterized in that: It is prepared by the method described in any one of claims 1-6 for preparing carbon-coated iron-cobalt nanoparticles with high saturation magnetization and low coercivity.

8. The carbon-coated iron-cobalt nanoparticles with high saturation magnetization and low coercivity according to claim 7, characterized in that: Its saturation magnetization is 105–180 emu / g, and its coercivity is 60–140 Oe.

9. The carbon-coated iron-cobalt nanoparticles with high saturation magnetization and low coercivity according to claim 7 or 8, characterized in that: Its iron-cobalt alloy molar content is 10% to 40%.

10. The application of carbon-coated iron-cobalt nanoparticles with high saturation magnetization and low coercivity as described in any one of claims 7-9 in soft magnetic devices.